Emulsions Made of Oils from Seeds of GM Flax Protect V79 Cells against Oxidative Stress. (8th December 2015) - Skorkowska-Telichowska, Katarzyna; Hasiewicz-Derkacz, Karolina; Gębarowski, Tomasz; Kulma, Anna; Moreira, Helena; Kostyn, Kamil; Gębczak, Katarzyna; Szyjka, Anna; Wojtasik, Wioleta; Gąsiorowski, Kazimierz
Abstract : Polyunsaturated fatty acids, sterols, and hydrophilic phenolic compounds are components of flax oil that act as antioxidants. We investigated the impact of flax oil from transgenic flax in the form of emulsions on stressed Chinese hamster pulmonary fibroblasts. We found that the emulsions protect V79 cells against the H2 O2 and the effect is dose dependent. They reduced the level of intracellular reactive oxygen species and protected genomic DNA against damage. The rate of cell proliferation increased upon treatment with the emulsions at a low concentration, while at a high concentration it decreased significantly, accompanied by increased frequency of apoptotic cell death. Expression analysis of selected genes revealed the upregulatory impact of the emulsions on the histones, acetylases, and deacetylases. Expression of apoptotic, proinflammatory, and anti-inflammatory genes was also altered. It is thus suggested that flax oil emulsions might be useful as a basis for biomedical products that actively protect cells against inflammation and degeneration. The beneficial effect on fibroblast resistance to oxidative damage was superior in the emulsion made of oil from transgenic plants which was correlated with the quantity of antioxidants and squalene. The emulsions from transgenic flax are promising candidates for skin protection against oxidative damage.